2014
DOI: 10.1039/c3fo60411j
|View full text |Cite
|
Sign up to set email alerts
|

A novel macromolecular extract screened from satsuma with pro-inflammatory effect

Abstract: Excessive consumption of horticultural fruit is a double-edged sword with both positive and negative effects. In Eastern countries, a large number of people have suffered from shang huo as a result of excessive consumption of "heating" foods, such as lychee, longan, mandarin orange, mango and civet durian. The present study adopted a step by step strategy screened the compositions with pro-inflammatory effect in satsuma fruits. The pro-inflammatory effects of all fractions were evaluated in RAW 264.7 cell line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…Based on previous studies by Yan et al 7 and Huang et al , 3 we found that the pro-inflammatory components of litchi were present in water-soluble extracts and were likely to be proteins. The LWP extract from litchi fruit significantly activated the release of the pro-inflammatory mediators IL-1β , iNOS and COX-2 , and the anti-inflammatory mediator HO-1 in the RAW264.7 murine macrophage cell line.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Based on previous studies by Yan et al 7 and Huang et al , 3 we found that the pro-inflammatory components of litchi were present in water-soluble extracts and were likely to be proteins. The LWP extract from litchi fruit significantly activated the release of the pro-inflammatory mediators IL-1β , iNOS and COX-2 , and the anti-inflammatory mediator HO-1 in the RAW264.7 murine macrophage cell line.…”
Section: Discussionmentioning
confidence: 61%
“…In our previous study, we found that pro-inflammatory substances of the ‘heating’ fruit satsuma consisted of specific proteins by performing a systematic screen of substances from satsuma fruit in the RAW264.7 murine macrophage cell line. 7 In contrast, LPS-induced prostaglandin E2 production was inhibited by an extract from the ‘cooling’ fruit bitter gourd. The expression levels of NF-kappa B, iNOS and COX-2 proteins were significantly inhibited by wild bitter gourd extracts.…”
Section: Introductionmentioning
confidence: 98%
“…Each protein gel band was destained, cleaned, and digested in-gel with sequencing grade modified trypsin, as described in literature (Thangthaeng et al, 2011 ; Yan et al, 2014 ).…”
Section: Methodsmentioning
confidence: 99%
“…The protein identification work was carried out at ProtTech Inc. (Phoenixville, PA, USA) using the Nano-LC-ESI-MS/MS for peptide sequencing, which can identify proteins with an ultra-high sensitivity. The same service with similar HPLC and LC-MS/MS settings has been used successfully in numerous proteomic analyses in literature (Thangthaeng et al, 2011 ; Abdelmegeed et al, 2013 ; Yan et al, 2014 ; Li et al, 2015 ). Briefly, the above prepared, trypsin-digested peptides mixture was subjected to a LC-MS/MS system, in which HPLC with a reverse phase C18 column (75 μm ID) was in-line coupled to a quadrupole ion trap mass spectrometer (LCQ Deca XP PLUS, Thermo, Palo Alto, CA).…”
Section: Methodsmentioning
confidence: 99%
“…Certain foods, such as litchi, longan, mango, durian, orange, chili, pepper, etc., are known as "heating" food in traditional Chinese medicine. Excessive consumption of "heating" foods by some people can cause a number of disorders such as red and swollen eyes, acne, sores and ulcers in the mouth and tongue, swollen gums, sore throat, yellow urine, constipation and other symptoms, which are known as "shanghuo" (heating-up) in Chinese medicine [1][2][3] . Studies have shown that "heating" foods such as litchi and citrus cause "shanghuo" mainly through systemic low-grade in ammatory reactions caused by some macromolecular substances in food, but the exact mechanism is not clear [4][5][6] .…”
Section: Introductionmentioning
confidence: 99%